2017
DOI: 10.7150/ijms.18075
|View full text |Cite
|
Sign up to set email alerts
|

Improving on Laboratory Traumatic Brain Injury Models to Achieve Better Results

Abstract: Experimental modeling of traumatic brain injury (TBI) in animals has identified several potential means and interventions that might have beneficial applications for treating traumatic brain injury clinically. Several of these interventions have been applied and tried with humans that are at different phases of testing (completed, prematurely terminated and others in progress). The promising results achieved in the laboratory with animal models have not been replicated with human trails as expected. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 119 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…However, many promising therapies in pre-clinical models failed to provide beneficial outcomes in clinical trials, at least in part because of critical differences between pre-clinical models and the clinical setting. 52 Because ICP is one of the most important aspects of sTBI patient care, further pre-clinical studies using animal models that adequately replicate the challenges of ICP management, as well as other aspects of TBI in the clinical setting, are essential for clinicians to better understand the association of ICP with other injury mechanisms and TBI severity.…”
Section: Current Status Of Brain Monitoring In Experimental Models Ofmentioning
confidence: 99%
“…However, many promising therapies in pre-clinical models failed to provide beneficial outcomes in clinical trials, at least in part because of critical differences between pre-clinical models and the clinical setting. 52 Because ICP is one of the most important aspects of sTBI patient care, further pre-clinical studies using animal models that adequately replicate the challenges of ICP management, as well as other aspects of TBI in the clinical setting, are essential for clinicians to better understand the association of ICP with other injury mechanisms and TBI severity.…”
Section: Current Status Of Brain Monitoring In Experimental Models Ofmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is an acquired form of injury to the brain caused by an external force that results in either mild, moderate, or severe neurological dysfunction. Animal models reproducing different types of TBI, including focal contusions/penetrating injuries with uid percussion or weight-drop devices and diffuse/non-penetrating injuries with blast tubes or also weight-drop devices, have observed in ammation, edema, oxidative stress, and blood-brain barrier breach following the insult and corresponding to behavioral de cits [1][2][3][4]. One of the major pathological events of TBI is intracranial and, subsequently, intracerebral hemorrhaging including epidural, subdural, subarachnoid, and intraventricular hematomas [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Animal models have been used to reproduce different types of TBI such as focal contusions/penetrating injuries done with uid percussion or weight-drop devices to administer the injury as well as diffuse/non-penetrating injuries done with blast tubes or also weight-drop devices [1,2]. These studies have observed in ammation, edema, oxidative stress, and blood-brain barrier breach with corresponding behavioral de cits following the insult [3][4][5][6][7]. One of the major pathological events of TBI is intracranial and, subsequently, intracerebral hemorrhage including epidural, subdural, subarachnoid, and intraventricular hematoma [8,9].…”
Section: Introductionmentioning
confidence: 99%